How Does the Economic Uncertainty Affect Asset Prices under Normal and Financial Distress Times? - Mehmet Balcilar; Zeynel Abidin Ozdemir; Huseyin Ozdemir; Gurcan Aygun; Mark E. Wohar (Institute of Labor Economics (IZA), 2022)
By using a nonlinear VAR model, we investigate whether the response of the US stock and housing markets to uncertainty shocks depends on financial conditions. Our model allows us to change the response of the US financial markets to volatility shocks in periods of normal and financial distress. We find strong evidence that uncertainty shocks have adverse effects on the US financial markets, irrespective of financial conditions. Moreover, our empirical results show that the rebound in US housing prices, which fell sharply in the economic turmoil, is state-dependent. This reflects the Fed's expansionary monetary policy to stabilize the US housing market. Furthermore, our findings reveal that economic agents who closely monitor the impact of uncertainty on the US stock and housing markets should also consider financial frictions in the US economy.
Keywords: C32; E32; E44; G01; G12; R31; 330; asset prices; economic uncertainty; financial conditions; regime switching; US